Novi oblici ugroza i nacionalna sigurnost u percepciji hrvatskih građana - Ogorec, Marinko (Array, 2009)
New challenges and threats of an unconventional and untraditional nature have put forward the problem of the socalled "non-military security threat", i.e. military conflict which does not take place according to international conventions and rules due to which a new concept of "asymmetric warfare" has been adopted. A great number of European countries (including the Republic of Croatia) estimate that classical conventional attack on a country’s territory in the current constellation of international relations is not likely, but on the other hand, the likelihood of unconventional forms of security threats occurring has greatly increased. In this context, a research has been conducted whose aim was to determine the attitudes of the public towards the perception of contemporary threats and their possible use to threaten the population of the Republic of Croatia.